2017
DOI: 10.1002/phar.2027
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Use of Olaparib for the Treatment of Metastatic Castration‐Recurrent Prostate Cancer

Abstract: Although mortality from prostate cancer has declined over the past 20 years as a result of early detection and treatment, the 5-year survival rate for men with prostate cancer who develop metastatic disease is only 29%. Current treatment options for metastatic castration-recurrent prostate cancer (mCRPC) are associated with toxicity and a limited durable response; therefore, additional lines of efficacious and minimally toxic therapy are needed. Olaparib, a poly(adenosine 5'-diphosphate) ribose polymerase (PAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 42 publications
(109 reference statements)
0
17
0
Order By: Relevance
“…Other recent findings suggest that loss of the chromatin remodeler chromodomain-helicase-DNA-binding protein 1 (CHD1), which is often observed in advanced prostate cancer, increases the response to PARP inhibitors [ 79 , 80 ]. The encouraging clinical phase 2 results obtained with olaparib led to a breakthrough designation by the FDA and a phase 3 pivotal study is currently ongoing [ 81 ]. Conversely, the clinical results obtained for the PARP inhibitor veliparib given to mCRPC patients in addition to abiraterone acetate did not show a statistically significant improvement [ 82 ].…”
Section: Treatment Options and Potential Novel Therapiesmentioning
confidence: 99%
“…Other recent findings suggest that loss of the chromatin remodeler chromodomain-helicase-DNA-binding protein 1 (CHD1), which is often observed in advanced prostate cancer, increases the response to PARP inhibitors [ 79 , 80 ]. The encouraging clinical phase 2 results obtained with olaparib led to a breakthrough designation by the FDA and a phase 3 pivotal study is currently ongoing [ 81 ]. Conversely, the clinical results obtained for the PARP inhibitor veliparib given to mCRPC patients in addition to abiraterone acetate did not show a statistically significant improvement [ 82 ].…”
Section: Treatment Options and Potential Novel Therapiesmentioning
confidence: 99%
“…This genetic instability of tumor cells with HRR mutations makes them vulnerable to cell death via PARP inhibitors. [1] Olaparib, a PARP inhibitor, received the United States Food and Drug Administration breakthrough therapy designation in January 2016[1] on the basis of the novel TOPARP-A trial,[2] for mCRPC patients with ATM or BRCA1/2 gene mutations who have received prior taxane-based chemotherapy or enzalutamide/abiraterone. Based on the preclinical studies suggesting synergistic activity[3] with androgen deprivation, a randomized, double-blinded, placebo-controlled Phase II trial comparing combination of olaparib with abiraterone in mCRPC irrespective of HRR gene mutations was recently published in the Lancet Oncology on June 4, 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Although an important breakthrough, its applicability is limited only to patients with BRCA1/2 or ATM gene mutations. [1] Asim et al [3] in a genetic study demonstrated the concept of “synthetic lethality,” whereby androgen receptor inhibition leads to an increase in PARP activity, as occurs in cells with HRR mutations. Their study suggested the synergy between PARP inhibitors and drugs inhibiting androgen synthesis, forming the background for this study.…”
Section: Commentarymentioning
confidence: 99%
“…This becomes a critical component for cancer cell survival [168]. PCs with DNA repair gene alterations have found to be sensitive to PARP inhibitors [169]. To this end, the PARP suppression in mCRPC first assessed in the TOPARP-A trial, which was significant for high response rates (88%) in patients with DNA repair gene deficits [170].…”
Section: Prostate Cancermentioning
confidence: 99%